Al-Mutayyasarid according to Abd al-Khaliq al-Rikabi, a novel (The Seventh Days of Creation ((Critical study) - Jinan Hussein Khnyab Darraji , Dr . Bahar Siddiqui (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this study we dealt with the phenomenon of meta narration in the Iraqi novel, and it tries to answer the following questions: Does the modern narration exceed the limits of alliteration in the Arabic language, has the contemporary narration crossed the boundaries of the gender? One of its importance is to shed light on the meta, narrating this phenomenon, and the study aims at opinions on what it is called a meta narrative and its dimensions, and it includes three investigations, the first topic: that our endeavor faces an important obstacle - the theory of knowledge, because the Iraqi criticism, while using modern narrative theses, is a thesis ( Beyond the Narration). It should be, especially (metafiction / performance / meta realism). As for the second topic, the concepts of the modern Iraqi novel, because what worries us about it is the Iraqi novel and the law of the effect of change of homogeneity between the sexes on he - she. The Iraqi novel took a modern narrative - two sides intertwined, though not clear enough: The first: a modern narration with channels based on the balance between presentation, nature / message and symbol / private and public / appears. The subject and the subject, and perhaps the most important symbol of this process: Abd al-Khaliq al-Rikabi in the novel (The Seventh Day of Creation) as a fictional arkology story consisting of seven graded layers, in which Abd al-Khaliq al-Rikabi appears. Pose himself - the seventh narrator